ANALISIS KESULITAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM KELAS III DI SDN 1 SUKARAME - Santiani, Lisna; K. Adiredja, Radji (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
One of the important components in the education system is the curriculum. But in reality, not a few teachers have experienced difficulties in implementing the 2013 curriculum. This research is motivated by the difficulty of teachers in implementing 2013 curriculum in SDN 1 Sukarame. The focus of research in this study is (1) how teachers implement the 2013 curriculum (2) teacher difficulties in implementing the 2013 curriculum (3) the factors that cause teachers to implement the 2013 curriculum. the obectives of this study are (1) to describe the difficulties of teachers in implementing the 2013 curriculum (2) to describe how tearhers implement the 2013 curriculum (3) to describe the factors that cause teachers to implement the 2013 curriculum. the type of research used is descriptive qualitative research. Data collection is carried out through the estages of reduction, data presentation, and drawing conclusions. The results of the study show that there are several difficulties experienced by teachers in implementing the 2013 curriculum namely from difficulties in planning,implementation and assesment